Analisi Kontribusi dan Efektivitas Penetapan NJOP Berdasarkan Perhitungan Pajak Daerah Pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Kata Gunungsitoli - Zebua, Fransiska Riang Hati; Buulolo, Nanny A.; Harefa, Idarni; Zai, Kurniawan S. (Visi Sosial Humaniora, 2024)
The realization of land and building tax in the Gunungsitoli City Government in 2021-2022 does not correspond to the level of contribution and effectiveness in PAD revenue which is still classified as very low. This research aims to analyze how big the contribution and effectivenes of land building taxes is in increasing the Regional Original Income of Gunungsitoli City. The research method used is a quantitative descriptive method that uses secondary data and literature with the data source coming from the Regional Financial and Revenue Management Agency (RFRMA) of Gunungsitoli City. In this research, the time period used was 2021-2022 with data analysis using overlay analysis techniques. The research results show that the contribution value is carried out using a tax and levy revenue matrix based on an overlay analysis for 2021-2022. In the 2 (two) year period from 2021 - 2022, the value of the land and building tax contribution includes the criteria for very less in contributing to local original.